The Direct Relationship between Animal Health and Food Safety Outcomes - Hurd, Scott; Masters, Barbara; Mathew, Alan; Oliver, Steve; Preston, Rod; Singer, Randall S. (Council for Agricultural Science and Technology (CAST), 2012)
The health of the animals within the food animal production system impacts many aspects of the system far removed from the animals themselves. To promote high productivity in animal agriculture, researchers need to examine nutrition, management systems, and animal care practices including the use of antibiotics and vaccines. This Commentary looks at the pressures to change livestock rearing methods, evidence to support the direct public health impact on human illness days, and good safety and inspection service regulations. The authors use indirect evidence, diagrams, and graphs to deliver their findings about the ways that healthy animals result in safer food.